2020
DOI: 10.3390/su12020646
|View full text |Cite
|
Sign up to set email alerts
|

Freeway Short-Term Travel Speed Prediction Based on Data Collection Time-Horizons: A Fast Forest Quantile Regression Approach

Abstract: Short-term traffic speed prediction is vital for proactive traffic control, and is one of the integral components of an intelligent transportation system (ITS). Accurate prediction of short-term travel speed has numerous applications for traffic monitoring, route planning, as well as helping to relieve traffic congestion. Previous studies have attempted to approach this problem using statistical and conventional artificial intelligence (AI) methods without accounting for influence of data collection time-horiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 65 publications
0
18
0
1
Order By: Relevance
“…Most of the existing traffic control schemes deploy fixed time program are based on historical traffic information without considering real-time traffic information [49]. Accurate short-term traffic sate prediction have been reported to have numerous applications for intelligent traffic control [50,51]. Numerous research studies have focused on minimizing delay through signalized intersections by rationally optimizing the cycle length.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Most of the existing traffic control schemes deploy fixed time program are based on historical traffic information without considering real-time traffic information [49]. Accurate short-term traffic sate prediction have been reported to have numerous applications for intelligent traffic control [50,51]. Numerous research studies have focused on minimizing delay through signalized intersections by rationally optimizing the cycle length.…”
Section: Previous Studiesmentioning
confidence: 99%
“…These parametric approaches require high-quality data where the sequence needed to be stable and accurate. As most real-life traffic data are unstable and stochastic, this has limited their use and applicability in complex traffic prediction applications [22].…”
Section: Parametric Approachesmentioning
confidence: 99%
“…The authors validated the feasibility of their modeling approach on Beijing's Third Ring Road. A recent study conducted by Zahid et al, proposed a new ensemble-based Fast forest quantile regression (FFQR) method to forecast short-term travel speed prediction [48]. It was concluded that proposed approach yielded robust speed prediction results, particularly at larger time-horizons.…”
Section: Related Workmentioning
confidence: 99%